How can we achieve more sustainable water allocation in water-deficient areas? A case study from China’s Fen River Basin - Li, Chenchen; Wu, Jianwei (Frontiers in Environmental Science, 2023)
It is significant for the ecological conservation of the basins that achieving the goal of water resources allocation improvement. Considering the water supply and demand contradiction and the competition among stakeholders within water-deficient regions, we developed a multi-objective optimization model and proposed the most effective method for allocating water resources based on the study of supply and demand. This study reveals the following findings: (1) The total demand for the Fen River Basin in 2030 will be 6.68 billion m 3 . Compared with previous years, actual consumption has risen, but the growth rate has slowed down. (2) The basin's total supply of water in 2030 will be 7.855 billion m 3 . With the tightening of the management practice, the consumption and supply in each county showed a trend of the decreasing year by year. (3) The results of allocation in 2030 are that 1.655 billion m 3 of domestic water, 4.57 billion m 3 of production consumption, and 57 million m 3 of ecological use.